2024
DOI: 10.1037/xge0001479
|View full text |Cite
|
Sign up to set email alerts
|

Object-based encoding constrains storage in visual working memory.

William X. Q. Ngiam,
Krystian B. Loetscher,
Edward Awh

Abstract: The fundamental unit of visual working memory (WM) has been debated for decades. WM could be objectbased, such that capacity is set by the number of individuated objects, or feature-based, such that capacity is determined by the total number of feature values stored. The present work examined whether object-or feature-based models would best explain how multifeature objects (i.e., color/orientation or color/shape) are encoded into visual WM. If maximum capacity is limited by the number of individuated objects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(117 reference statements)
1
5
0
Order By: Relevance
“…The authors concluded that the units of WM are objects in which all their visual features are integrated. Further studies argued in favor of this strong object hypothesis, showing that only objects, not individual features, count towards the load on the capacity of working memory (Cowan et al, 2013;Luria & Vogel, 2011;Ngiam et al, 2023;Vogel et al, 2001;Zhang & Luck, 2008). In addition, neuroimaging studies identified object-based markers of the contents of working memory.…”
Section: Bindings In Visual Working Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the units of WM are objects in which all their visual features are integrated. Further studies argued in favor of this strong object hypothesis, showing that only objects, not individual features, count towards the load on the capacity of working memory (Cowan et al, 2013;Luria & Vogel, 2011;Ngiam et al, 2023;Vogel et al, 2001;Zhang & Luck, 2008). In addition, neuroimaging studies identified object-based markers of the contents of working memory.…”
Section: Bindings In Visual Working Memorymentioning
confidence: 99%
“…As long as any unit in memory can be accessed at all, all its elements can be reported; if it happens to be the wrong unit, then all reported elements come from the same wrong unit. This model implements the all-or-none assumption associated with the strong object hypothesis about visual working memory (e.g., Cowan, 2001;Hollingworth & Henderson, 2002;Ngiam et al, 2023;Rensink, 2000). 1b).…”
Section: Present Studymentioning
confidence: 99%
“…Facing the strengthening of attention, the refocused object representation reveals lower initial quality than focused one, unavoidably causing the distinctive performances in single-and double-cue conditions despite of no variability in attention's improvement effect on representations. However, dimension-based focus or refocus is hard to go over to this integrated-object unit (Luria and Vogel 2014;William X. Q. Ngiam, Loetscher, and Awh 2024;Vogel, Woodman, and Luck 2001), and it is uneconomical to split integrated representations and give up the uncued dimension which is tightly bound with the focused dimension, especially when the uncued dimension in VWM might be also relevant. With a constant rehearsal of integrated representations to sustain comparable baseline state of each dimension in VWM, dimension-based attention flexibly shifts between dimensions and switches participants' preparation for each dimension.…”
Section: Attention Shift Cost For Objects Rather Than Dimensionsmentioning
confidence: 99%
“…The integration effect for objects in VWM indicates a consensus on integrated representations based on context (Oberauer and Lin 2023;Postle and Postle 2020) or some principles like the Gestalt (T. Gao et al 2011;Z. Gao et al 2022), despite the multifarious terms of VWM integrated units (object-based representations: Awh et al, 2007;Ngiam et al, 2024;Vogel et al, 2001;pointers: Balaban et al, 2019;Thyer et al, 2022;tokens: Ngiam, 2023). It is incredible that attention selectively removes one dimension but protects or strengthens the other one when these dimensions occupy the totally same context and are hard to be distinguished in terms of locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation